Assessing the Health Impact of the following Measures in Schools in Maradi (Niger): Construction of Latrines, Clean Water Supply, Establishment of Hand Washing Stations, and Health Education. (19th January 2014) - Boubacar Maïnassara, Halima; Tohon, Zilahatou
Abstract : Objective. To assess the effect on health of the following measures in schools in Maradi (Niger): clean water supply, construction of latrines, establishment of hand washing stations, and health education. Methodology. It was a "before and after" intervention study on a sample of school children aged 7 to 12 years in the Maradi region. The interventions included building of latrines, supplying clean water, setting up hand washing stations, and teaching health education lessons. An individual questionnaire, analysis of stool samples, and a group questionnaire were administered to children and teachers, respectively. The threshold for significance was set atP < 0.05 . Results . A statistically significant reduction in cases of diarrhoea and abdominal pains was noted after the project. Overall, carriage of at least one parasite increased from 7.5% before the project to 10.2% after it (P = 0.04 ). In the programme group schools, there was a statistically significant increase in the prevalence of Hymenolepis nana, from 0 to 1.9 (P = 0.02 ). Pinworm prevalence remained stable in this group but increased significantly in the control group. Conclusions. Putting health infrastructure in place in schools obviously had an impact on hygiene-related habits in the beneficiary schools and communities.